Validation of Protein A chromatography: orthogonal method with size exclusion chromatography validation for mAb titer analysis - Sahinkaya Elif; Ozkan Aylin; Ozdemir Nilay; Aslan Merve Elif; Bicak Dilan; Cakir Nilufer; Oncel Hatice; Yetimoglu Ece Kok (Türk Biyokimya Dergisi)
After reviewing the reference product specifications, found that they include the SEC HPLC result but do not specify Protein A chromatography as a test. Although there is no record of reference product specifications, alternative methods are necessary, particularly for routine analysis of biotechnological products.